Does healthy lifestyle contribute to physical and mental health among University students? - Widyasari, Dian Caesaria; Turnip, Sherly Saragih (Makara Journal of Health Research, 2019)
Background: Little is known of how a healthy lifestyle and its health outcomes are related in university students in Indonesia. This study examined the association between healthy lifestyle markers (diet, sleeping hours, physical exercise, smoking, alcohol intake) and health outcomes (perceived physical fitness, psychological distress) among undergraduate students at university in Indonesia. We also examined gender-related patterns. Methods: A total of 616 undergraduate students participated in two cross-sectional studies carried out between 2011 and 2013. Six close-ended questions were used to measure health behaviors and perceived physical fitness. The Hopkin Symptoms Checklist-25 was used to measure psychological distress. Results: The results showed gender differences in physical exercise, smoking, and alcohol intake. A healthy diet, regular physical exercise, and adequate sleeping hours were identified as contributing factors for perceived physical fitness. The probability of experiencing mental health problems was 65% higher among sedentary students and being female doubles this risk. Conclusion: Engagement in physical exercise consistently contributes to both measures of health outcome. Further, this study found that female students had greater susceptibility to health issues due to a sedentary lifestyle than male ones.